Principles of geotechnical engineering - Das, Braja M. ([S.l.] : Thomson-Engineering, 2001)
Braja M. Das' PRINCIPLES OF GEOTECHNICAL ENGINEERING provides civil engineering students and professionals with an overview of soil properties and mechanics, combined with a study of field practices and basic soil engineering procedures. Through four editions, this book has distinguished itself by its exceptionally clear theoretical explanations, realistic worked examples, thorough discussions of field testing methods, and extensive problem sets, making this book a leader in its field. Das's goal in revising this best-seller has been to reorganize and revise existing chapters while incorporating the most up-to-date information found in the current literature. Additionally, Das has added numerous case studies as well as new introductory material on the geological side of geotechnical engineering, including coverage of soil formation.